2011
DOI: 10.1158/1078-0432.ccr-10-2772
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 Is Overexpressed Waldenström Macroglobulinemia and Its Inhibition by Dovitinib Induces Apoptosis and Overcomes Stroma-Induced Proliferation

Abstract: Purpose: There is no standard of therapy for the treatment of Waldenstr€ om macroglobulinemia (WM), therefore there is a need for the development of new agents. Fibroblast growth factor receptor 3 (FGFR3) was shown to play a major role in several types in cancer. Dovitinib, an inhibitor of FGFR3, was effective in hematologic malignancies. In this study, we tested FGFR3 as a therapeutic target in WM and tested the effect of dovitinib on cell proliferation and apoptosis of WM cells in the context of BM microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…To determine early differences in tumor growth patterns and to confirm that the cells did not loose siRNA inhibition, the mice were sacrificed after 1 week (21,22 (50-1,000 ng/mL) on SDF1-induced chemotaxis of BCWM1 cells. B, the effect of recombinant ephrin-B2 (50-1,000 ng/mL) on chemotaxis of BCWM1 cells using an 8-micron pore filters for transwell migration assay.…”
Section: Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…To determine early differences in tumor growth patterns and to confirm that the cells did not loose siRNA inhibition, the mice were sacrificed after 1 week (21,22 (50-1,000 ng/mL) on SDF1-induced chemotaxis of BCWM1 cells. B, the effect of recombinant ephrin-B2 (50-1,000 ng/mL) on chemotaxis of BCWM1 cells using an 8-micron pore filters for transwell migration assay.…”
Section: Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…Effect of tumor progression on hypoxia in Waldenstr€ om macroglobulinemia bone marrow BCWM.1 cells were genetically engineered to express mCherry fluorescent protein and luciferase (Luc), as described previously (5). Human BCWM.1-mCherry cells were injected into 12 SCID mice intravenously at different concentrations of 0.5 Â 10 6 , 1 Â 10 6 , and 2.5 Â 10 6 cells per mouse (4 mice per condition) and allowed to grow for 3 weeks.…”
Section: Animalsmentioning
confidence: 99%
“…The Waldenstr€ om macroglobulinemia cells infiltrate specifically into the bone marrow niche which implies the critical role of the bone marrow as a supportive microenvironment for the Waldenstr€ om macroglobulinemia cells due to the various interactions (2)(3)(4). We have previously shown in Waldenstr€ om macroglobulinemia that the bone marrow milieu promotes tumor progression including cell proliferation, survival, and drug resistance through production of cytokines, regulation of cell interaction, cell adhesion with stroma and endothelial cells, and cell trafficking (3,(5)(6)(7). We have also shown before that the bone marrow microenvironment plays a crucial role in the progression and drug resistance of other hematologic malignancies including multiple myeloma (8)(9)(10) and chronic myeloid leukemia (CML; refs.…”
Section: Introductionmentioning
confidence: 99%
“…2I ). Recently, overexpression of FGFR3 has been reported in Waldenstrom macroglobulinemia (WM) and that inhibition of FGFR3 induces apoptosis in WM cells and overcomes stromal protection 14 . Of interest, we also found that while in vitro combined treatment of CLL B-cells with TKI-258 and ibrutinib produced synergistic effects in 5 of 7 cases ( Fig.…”
mentioning
confidence: 99%